2006
DOI: 10.1177/13670069060100040201
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of phonological development and language dominance in bilingual Cantonese-Putonghua children

Abstract: The study investigated similarities and differences in the development of the Cantonese and the Putonghua phonology of children becoming bilingual in those languages with different dominant languages. One hundred children living in Hong Kong or in Shenzhen and aged from 2;6—4;11, who were simultaneously acquiring Cantonese and Putonghua provided the data we report. The Cantonese Segmental Phonology Test (So, 1993) and the Putonghua Segmental Phonology Test (So & Zhou, 2000) were used to elicit phonemes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
36
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 19 publications
6
36
1
Order By: Relevance
“…Thus, the Welsh clusters contained more sounds that are known to be acquired late in singletons, such as /r/, // and // (Ball et al, 2001a(Ball et al, , 2001b, than the English ones. This finding is consistent with Law and So's (2006) study of Cantonese-Putonghua bilingual children, which revealed that both Cantonesedominant and Putonghua-dominant bilinguals developed Cantonese phonology faster than the more complex phonology of Putonghua. Law and So's (2006) study also exhibited symmetrical dominance effects: the Cantonese-dominant bilinguals outperformed the Putonghua-dominant ones on Cantonese phonology, and the Putonghua-dominant bilinguals the Cantonese-dominant ones on Putonghua phonology.…”
Section: Cluster Acquisition and Dominancesupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the Welsh clusters contained more sounds that are known to be acquired late in singletons, such as /r/, // and // (Ball et al, 2001a(Ball et al, , 2001b, than the English ones. This finding is consistent with Law and So's (2006) study of Cantonese-Putonghua bilingual children, which revealed that both Cantonesedominant and Putonghua-dominant bilinguals developed Cantonese phonology faster than the more complex phonology of Putonghua. Law and So's (2006) study also exhibited symmetrical dominance effects: the Cantonese-dominant bilinguals outperformed the Putonghua-dominant ones on Cantonese phonology, and the Putonghua-dominant bilinguals the Cantonese-dominant ones on Putonghua phonology.…”
Section: Cluster Acquisition and Dominancesupporting
confidence: 92%
“…This finding is consistent with Law and So's (2006) study of Cantonese-Putonghua bilingual children, which revealed that both Cantonesedominant and Putonghua-dominant bilinguals developed Cantonese phonology faster than the more complex phonology of Putonghua. Law and So's (2006) study also exhibited symmetrical dominance effects: the Cantonese-dominant bilinguals outperformed the Putonghua-dominant ones on Cantonese phonology, and the Putonghua-dominant bilinguals the Cantonese-dominant ones on Putonghua phonology. This finding differs from the asymmetrical dominance patterns observed in the present study in which the Welsh-dominant bilinguals acquired the Welsh clusters earlier and with greater accuracy than the English-dominant bilinguals, without thereby lagging behind on the English clusters.…”
Section: Cluster Acquisition and Dominancesupporting
confidence: 92%
“…They suggested language dominance "may help to prevent unusual speech patterns from occurring" [18] and that dominant language should be less influenced by bilingualism [30]. On the other hand, Law and So [19] specifically addressed the issue of language dominance with 100 bilingual children and found that bilingual children produced typical error patterns comparable to monolingual children, regardless of language dominance.…”
Section: Introductionmentioning
confidence: 99%
“…To account for both 'atypical' and 'delayed' error patterns in bilingual children, the literature has offered explanations relating to differences in phonological typologies in the languages to which bilingual children are exposed [e.g. 19,23,25,27,29,31]. According to Dodd, So [25], bilingual children produce 'atypical' error patterns when the languages to which they are exposed markedly differ in the constraints that limit the segmentation of speech signals.…”
Section: Introductionmentioning
confidence: 99%
“…A language is considered dominant when it is preferred and frequently used in comparison to another language (Law & So, 2006). This is especially true with young Singaporean children as they are still at the early stages of learning both languages.…”
Section: Language Dominance In Singaporean Bilingual Childrenmentioning
confidence: 99%